THE EFFECT OF SCRIPT BASED IMPROVISATION ON THE SPEAKING ACHIEVEMENT AT SMA NEGERI 2 BUSUNGBIU - Setiawan, I Md. (Universitas Pendidikan Ganesha, 2019)
AbstractThis study was intended to investigate whether or not there was a significant effect in speaking achievement between the students who were taught by Script – Based Improvisation and the students who were taught by memorizing dialogue technique as conventional strategy. The population of this study was the students of grade eleventh in SMA N 2 Busungbiu and the samples were selected randomly by using Cluster Random Sampling technique. From the lottery, it was found that class XI IPA 1 was experimental group and XI IPA 2 was the control group. The hypothesis used in this study was alternative hypothesis which stated there was significant difference between two groups of students taught through Script–Based Improvisation and Memorizing technique. Post – Test Only Control Group Design was applied as the research design. After six times of treatments, the posttest was administered to find out the impact of the treatment. From the data that were analyzed descriptively and inferentially, it was obtained that the mean score for Experimental group was 79.50 and the mean score for Control group was 75.46, while the value of to (t observed) was 3.064 and exceeded the tcv (t critical value) which was 1.96 (significance level 5 %). It indicated there was significant difference of speaking achievement between both Experimental and Control group that were treated differently.The key terms: Speaking, Speaking Achievement, Script – Based Improvisations